(untitled) (Third Sector Social Economic Review, 2023)
Social entrepreneurship is an entrepreneurial model in which social and economic phenomena are intertwined and it prioritizes creating a social value while developing new perspectives for the social system. Social enterprises are structures that aim sustainable progress through joint and local movements. They prioritize social transformation and benefit rather than economic gain and focus on solving social problems by gaining the support of the society in the long run. Cooperatives are models based on the principle of being responsible to society and they are social enterprises as they work for the sustainable development of the local communities. Women’s cooperatives, which aim to empower women socio-economically and reveal the importance of their social roles, are also accepted as social enterprises at the global and national level. This qualitative study was conducted to examine the social entrepreneurship dimension of women’s cooperatives and the own perceptions of social entrepreneurs who pioneered the establishment of cooperatives. The sample of the study consists of 8 women’s cooperatives in Denizli. The participants defined women’s cooperatives as social enterprises due to the social and economic values provided at individual and societal level and they defined themselves as social entrepreneurs because of their individual competencies and social networks.